Smarce1 and Tensin 4 Are Putative Modulators of Corneoscleral Stiffness - Boazak, Elizabeth M.; King, Rebecca; Wang, Jiaxing; Chu, Cassandra M.; Toporek, Aaron M.; Sherwood, Joseph M.; Overby, Darryl R.; Geisert, Eldon E.; Ethier, C. Ross (Frontiers in Bioengineering and Biotechnology, 2021)
The biomechanical properties of the cornea and sclera are important in the onset and progression of multiple ocular pathologies and vary substantially between individuals, yet the source of this variation remains unknown. Here we identify genes putatively regulating corneoscleral biomechanical tissue properties by conducting high-fidelity ocular compliance measurements across the BXD recombinant inbred mouse set and performing quantitative trait analysis. We find 7 cis-eQTLs and nonsynonymous SNPs associating with ocular compliance, and show by RT-qPCR and immunolabelling that only two of the candidate genes, Smarce1 and Tns4, showed significant expression in corneal and scleral tissues. Both have mechanistic potential to influence the development and/or regulation of tissue material properties. This work motivates further study of Smarce1 and Tns4 for their role(s) in ocular pathology involving the corneoscleral envelope as well as the development of novel mouse models of ocular pathophysiology such as myopia and glaucoma.